2022
DOI: 10.1002/pchj.558
|View full text |Cite
|
Sign up to set email alerts
|

How Chinese children's filial piety beliefs affect their parents’ life satisfaction and loneliness

Abstract: Filial piety (or xiao) is a unique Chinese culture that affects older adults’ life satisfaction and loneliness. Guided by the dual filial piety model and socioemotional selectivity theory, this study explores how adult children's filial piety beliefs affect their parent's life satisfaction and loneliness. A total of 350 pairs of parent–child data were collected through a parent–child pair design. Results show that emotional support provided by adult children and emotional support perceived by parents (i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…As such, individuals originated from typical Chinese families generally use a collective and family-centered approach as the basis for decision-making [ 7 ], which may end up with the sacrifice of true personal needs or feelings. In fact, it has been found that the implanted idea of filial piety in adult children is associated with the level of parental well-being, including higher life satisfaction and lower mortality [ 4 , 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, individuals originated from typical Chinese families generally use a collective and family-centered approach as the basis for decision-making [ 7 ], which may end up with the sacrifice of true personal needs or feelings. In fact, it has been found that the implanted idea of filial piety in adult children is associated with the level of parental well-being, including higher life satisfaction and lower mortality [ 4 , 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults with filial children can get more support from relatives and friends (27). Chinese children's filial beliefs affect their parents' life satisfaction and loneliness (28).…”
Section: Introductionmentioning
confidence: 99%